The Role of Digital Feedback on the Self-Esteem of Digital Natives - Şakir Güler; Murat Sezgin (Türkiye İletişim Araştırmaları Dergisi)
The development of web technologies makes virtual platforms as an inseparable part of human life. This situation makes digital feedback highly effective on the self-esteem of individuals. For this reason, the present research explores the relationship between the self-esteem of digital natives and their feedback from digital platforms. The participants of this study include 310 high school students in Isparta, Turkey and the study adopts Rosenberg’s Self-Esteem Scale (RSES), Digital Feedback Form (DFF), and Personal Information Form (PIF) in order to demonstrate the role of digital feedback on the self-esteem of digital natives. The previous studies in the literature were carried out on specific social media platforms, therefore they could not include all of the interaction opportunities. Since this research considers different types of feedback on social media, it provides a comprehensive knowledge in the field. This research demonstrates that there is a significant relation between the self-esteem levels of digital natives and the feedback that they receive in terms of “friend requests they send” and “posts they share being retweeted/reposted”. Thus, the results reveal that the self-esteem levels of adolescents vary based on the feedback that is related to the friendship requests, direct messages, reception of positive comments on posts and their tweets being retweeted/reposted.